Is this good science communication? Construction and validation of a multi-dimensional quality assessment scale from the audience’s perspective - Taddicken, Monika; Fick, Julian; Wicke, Nina (Frontiers in Communication, 2024)
The expansion of science communication (Bubela et al., 2009;Bucchi and Trench, 2014) underscores the increasing importance of understanding what constitutes good science communication (Niemann et al., 2023). This question concerns the public's understanding and engagement with science (Choung et al., 2020; Davies, 2013; Stilgoe et al., 2014). The scholarly discussion has shifted from the traditional deficit model to a more dialogue-oriented approach yet remains normatively anchored (Fähnrich, 2017;Mede and Schäfer, 2020). There is a pivotal lack of attention to the audience's perspective regarding the question of what good science communication is. Moreover, different formats of science communication have hardly been researched thus far.Therefore, this paper introduces a multi-dimensional scale to capture the audience's assessment of specific science communication formats. The development utilized a multi-step process to identify relevant criteria from both theoretical and practical perspectives. The instrument integrates 15 distinct quality dimensions, such as comprehensibility, credibility, fun, and applicability, structured according to different quality levels (functional, normative, user-, and communication-oriented). It considered theory-driven and practice-experienced categories and was validated through confirmatory factor analyses conducted on a German representative sample (n = 990). For validation, the scale was applied to a science blog post and a science video on homeopathy.After employing a seven-step process, we conclude that the newly devised scale effectively assesses the perceived quality of both blog and video science communication content. The overall assessment aligns with common target variables, such as interest and attitudes. The results regarding the different quality subdimensions provide a nuanced understanding of their contribution to the perceived overall quality. In this way, the scale aids in enhancing science communication in accordance with audience perceptions of quality. This marks the inaugural introduction of a comprehensive measurement instrument tailored to gauge quality from the audience's standpoint, rendering it applicable for utilization by both researchers and practitioners.